Education and Fertility: A Review of Recent Research in Europe - Sindhu Vasireddy; Ann Berrington; Bernice Kuang; Hill Kulu (Comparative Population Studies, 2023)
This paper reviews research on education and childbearing in Europe over the last decade. Early demographic research attributed declining fertility in advanced economies in the second half of the twentieth century to increasing female educational levels. The twenty-first century has witnessed further increases in educational attainment coupled with trend reversals in fertility. The relationship between education and fertility has become more complex, sparking renewed interest in the interplay between the two life domains. We examine how educational enrolment and attainment influence individuals’ fertility behaviour – both fertility timing and level – and how the relationship between education and fertility is shaped by contextual factors such as family policies, macroeconomic shocks, and normative changes in gender attitudes. We also summarise the recent literature on educational gradients in male fertility and review methodological developments to address issues of self-selection and unmeasured heterogeneity in the study of education and fertility. Finally, this paper identifies and discusses challenges and important areas for future research.